2016
DOI: 10.1038/srep20022
|View full text |Cite
|
Sign up to set email alerts
|

Experimental feline enteric coronavirus infection reveals an aberrant infection pattern and shedding of mutants with impaired infectivity in enterocyte cultures

Abstract: Feline infectious peritonitis (FIP) results from mutations in the viral genome during a common feline enteric coronavirus (FECV) infection. Since many virological and immunological data on FECV infections are lacking, the present study investigated these missing links during experimental infection of three SPF cats with FECV strain UCD. Two cats showed mild clinical signs, faecal shedding of infectious virus from 4 dpi, a cell-associated viraemia at inconsistent time points from 5 dpi, a highly neutralising an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 48 publications
2
37
0
3
Order By: Relevance
“…Detection of FCoV by RT-qPCR in colonic tissue of 3 cats without FIP was not surprising as enteric infection has been described in otherwise clinically healthy cats [7,8,32]. These 3 cats were euthanized as a result of clinical signs relating to pyothorax, brain tumour and nasal adenocarcinoma, had unremarkable histopathological examination and negative IHC of colonic tissue.…”
Section: Discussionmentioning
confidence: 94%
“…Detection of FCoV by RT-qPCR in colonic tissue of 3 cats without FIP was not surprising as enteric infection has been described in otherwise clinically healthy cats [7,8,32]. These 3 cats were euthanized as a result of clinical signs relating to pyothorax, brain tumour and nasal adenocarcinoma, had unremarkable histopathological examination and negative IHC of colonic tissue.…”
Section: Discussionmentioning
confidence: 94%
“…Mutations in other parts of the S 2 subunit than those affecting the proteolytic cleavage sites may also influence the tropism of different CoVs. Several studies report a correlation between mutations in the HR1 region of FCoVs and the conversion of FECV into FIPV (Bank-Wolf et al, 2014;Desmarets et al, 2016;Lewis et al, 2015). Such a correlation appeared even more convincing for mutations found in the recently identified FP2 (Chang et al, 2012;Ou et al, 2016).…”
Section: Other S 2 Mutations Associated With Altered Tropismmentioning
confidence: 89%
“…In several cases, FECVs remained detectable in the feces of the cats for more than 15 weeks, although with decreasing viral loads. To investigate the course of infection in more detail, FECV infection experiments have also been performed under controlled conditions (Desmarets et al, 2016;Kipar et al, 2010;Pedersen et al, 2008;Vogel et al, 2010). These studies showed that FECVs induce symptomless persistent infections similar to natural infections.…”
Section: Feline Enteric Coronavirusmentioning
confidence: 99%